A study of the collection management practices of selected Executive Government Department Libraries in Quezon City - Papa, Maria Amihan V.; Timoteo, Christine B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2019)
The study was conducted to assess the existing collection management practices of the libraries of the Department of Agriculture, Department of Environment and Natural Resources and Department of Agrarian Reform. The researcher tried to find out: 1) the collection management practices of the three libraries; 2) the factors that affect their collection management practices; 3) the strengths and weakness of their collection management practices and; 4) the changes needed by the libraries based on their weaknesses.
It was found out that the three libraries do not have written collection management practices. The factors that affect the collection management practices of the DA Library are the budget and the library space. The factors that affect the collection management practices of the DENR Centralized Library are the absence of a written collection management policy, library space, photocopying services and resource sharing. Lastly, the factors that affect the collection management practices of the BARIE Library are likewise the absence of a written collection management policy, staffing, acquisition and resource sharing.
The researcher concluded that the absence of written collection management policies might lead to biases and inconsistencies with regard to the process of selection and other components. The weaknesses of each library enter with their incompliance of the components of the collection management practices which does not really maximize the efficiency and role of a library. Despite the weaknesses, strengths emerge such as the libraries sticking to their respective mission and being user-oriented.
The study recommended the immediate drafting of the DA Library, DENR Centralized Library and BARIE Library's collection management policies, periodic evaluation, hiring of licensed librarians, more funding sources, engagement in resource sharing and practicing preservation to library materials.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Collection management (Libraries) -- Philippines -- Quezon City; Government libraries -- Philippines -- Quezon City